Design of semi-Z source inverter topology with reduced number switches for four quadrant control of direct current motor - Waseah Anjum; Sudeekshya Panda; Palanisamy Ramasamy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper proposes a novel approach to 4-quadrant speed control of a direct current (DC) motor based on the use of a semi-Z source inverter which has 2 active switches and 2 switching states. The semi-Z source inverter topology is analyzed for design purposes and results and relationships are discussed. The objective of this simulation is to design and analyze the performance of closed loop speed control of a DC motor using a semi-Z source inverter under realistic operating conditions. The findings of this project can be useful for designing several household appliances as well as systems like lathe machines, hoists, conveyors, and fans. Closed loop system designed for automatic speed control of a DC motor is obtained by using MATLAB/Simulink. The simulation results show that the proposed system works as intended.